Improving Dental and Oral Health Through Empowering Village Youth to Enhance Awareness Regarding the Importance of Dentures - Prabowo, Harly; Ariani, Maretaningtias Dwi; Kurdi, Abil; Rahmania, Primanda Nur; Sona, Nabila; Imani, Aurellia Della; Indrarini, Ratri; Wicaksono, Haryo Adhiweno; Ryani, Adelisa Devita (Indonesian Journal of Dental Medicine, 2024)
Background: Dental and oral health, which is an inseparable part of general body health, is still widely ignored since adolescence. Maintaining the integrity of teeth is an important part of dental and oral health. Tooth loss can cause functional, aesthetic, and social problems, reduce a person's quality of life, and can be an effective indicator of community oral health. Purpose: Empowering and educating about dental and oral health for adolescents to increase their awareness of dental and oral health. Method: Dental and oral health counseling and dental health examinations were conducted on 50 adolescents, students of Madrasah Aliyah Miftahul Ulum, Melirang, Gresik. This study included quantitative and qualitative methods to assess changes in knowledge and perceptions about denture care among participants. The stages of implementation carried out in this study included pre-test, counseling, question and answer, post-test, dental and oral examination. Results: The examination results showed that out of 50 teenagers at MA Miftahul Ulum, Melirang, Gresik, 0 used dentures, 0 had caries + missing teeth, 0 had missing teeth, 3 had restorations, 5 had caries + remaining roots, 9 had remaining roots, 9 had caries, and 29 had no abnormalities. The results of the post-test questionnaire showed an increase in insight, compared to the pre-test. Conclusion: The conclusion of the activity showed that there was an increase in adolescents' knowledge and understanding of dental and oral health, as well as the importance of using dentures.